TUGAS POKOK DAN FUNGSI KELEMBAGAAN DI DESA WISATA BATURETNO, BANGUNTAPAN, BANTUL - Eko Sugiarto; Suhartopo Suhartopo; Sabda Elisa Priyanto (LPPM Akademi Manajemen Administrasi Yogyakarta, 2023)
The mentoring activity for structuring the main tasks and institutional functions of the tourism village was carried out in the Baturetno Tourism Village, Baturetno Village, Kapanewon Banguntapan, Bantul Regency, Yogyakarta Special Region. This tourist community already has an institutional structure, but because some of the members are so busy, it isn't functioning at its best. As a result, some of them do many duties. The goal of this activity is to help the manager of the Baturetno Tourist Village organize the organizational structure and confirm the primary duties and responsibilities of each field in the organizational structure so that there are no overlaps. The methodology for conducting out the activity starts with a review of the literature and progresses to observations and interviews to learn more about the main responsibilities and institutional tasks of the tourist village. To be capable of providing the appropriate support, this is done in order to get a general understanding of the situation. One of the outcomes of this effort took the form of recommendations that were included in the Institutional Book for the Baturetno Tourist Village, which was created in collaboration with the manager of the tourism village.